FINAL REPORT ON PROPOSITION 99. PRESS/COMMUNICATIONS FINAL REPORT. - RAIMUNDO J (Tufts Archival Research Center, 2007)
Final report on the press/communications of the Californians Against Unfair Taxation (CAUTI) campaign. Discusses evolution of three separate phases of the media campaign. Provides recommendations about how to make each phase more successful. Discusses communication/outreach activities and press acitivities and contacts.